Effects of biostimulants on growth, yield and quality of Tomato (Solanum lycopersicum L) intercropped with palmyrah (Borrassus flabellifer L) - Nandhini , M; Manivannan , M I; Premalakshmi , V; Theradimani , M; Srinivasan , S; Sabarinathan , K G; Kennady, R N (Plant Science Today, 2025)
The present study aimed to investigate the impact of bio-stimulants on the growth and yield of Tomato (var. PKM-1) as an intercrop under Palmyrah plantation at the College Orchard of the Department of Horticulture, VOC Agricultural College and Research Institute, Killikulam, Thoothukudi district of Tamil Nadu during 2023-24. The maximum plant height at 30 (52.80 cm), 60 (73.40 cm) and 90 days after transplanting (86.47 cm), number of branches at 30 days after transplanting (3.20), 60 days after transplanting (7.60) and 90 days after transplanting (8.40), early flowering (26.2 days), 50 % flowering (39.8 days), individual fruit weight (30.29 g), number of fruits per plant (28.6), yield of fruits per plant (0.87 kg), yield per ha (31.97 ton per ha), chlorophyll a (0.89 mg per g), chlorophyll b (1.28 mg per g), total chlorophyll (1.65 mg per g), TSS (5.54° Brix), ascorbic acid content (23.87 mg per 100g), titrable acidity (0.65 %), lycopene content (2.47 mg per 100g)was recorded in (the 3 %) Panchagavya spray treatment. The salient findings revealed that among the different treatments, a 3 %Panchagavya spray demonstrated superiority in promoting the growth and yield of Tomato as an intercrop under Palmyrah in the dry land conditions of the Thoothukudi district. These findings highlight the potential of incorporating organic practices into intercropping systems suitable for arid and semi-arid regions.